2011
DOI: 10.1016/j.gca.2011.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Seawater nutrient and carbonate ion concentrations recorded as P/Ca, Ba/Ca, and U/Ca in the deep-sea coral Desmophyllum dianthus

Abstract: As paleoceanographic archives, deep sea coral skeletons offer the potential for high temporal resolution and precise absolute dating, but have not been fully investigated for geochemical reconstructions of past ocean conditions. Here we assess the utility of skeletal P/Ca, Ba/Ca and U/Ca in the deep sea coral D. dianthus as proxies of dissolved phosphate (remineralized at shallow depths), dissolved barium (trace element with silicate-type distribution) and carbonate ion concentrations, respectively. Measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
85
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 89 publications
10
85
0
1
Order By: Relevance
“…Case et al, 2010;Cohen et al, 2006;Gagnon et al, 2007;Lutringer et al, 2005;Montagna et al, 2006;Raddatz et al, 2013;RollionBard et al, 2009;Rüggeberg et al, 2008;Smith et al, 2000). To date only a few studies have focused on the reconstruction of the carbonate system using CWC skeletons (Anagnostou et al, 2011(Anagnostou et al, , 2012Blamart et al, 2007;McCulloch et al, 2012;Rollion-Bard et al, 2011a, b;Thresher et al, 2011). Coral uranium to calcium (U / Ca) ratios are known to depend on the carbonate system parameters (Anagnostou et al, 2011;Inoue et al, 2011;Min et al, 1995;Shen and Dunbar, 1995;Swart and Hubbard, 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Case et al, 2010;Cohen et al, 2006;Gagnon et al, 2007;Lutringer et al, 2005;Montagna et al, 2006;Raddatz et al, 2013;RollionBard et al, 2009;Rüggeberg et al, 2008;Smith et al, 2000). To date only a few studies have focused on the reconstruction of the carbonate system using CWC skeletons (Anagnostou et al, 2011(Anagnostou et al, , 2012Blamart et al, 2007;McCulloch et al, 2012;Rollion-Bard et al, 2011a, b;Thresher et al, 2011). Coral uranium to calcium (U / Ca) ratios are known to depend on the carbonate system parameters (Anagnostou et al, 2011;Inoue et al, 2011;Min et al, 1995;Shen and Dunbar, 1995;Swart and Hubbard, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…To date only a few studies have focused on the reconstruction of the carbonate system using CWC skeletons (Anagnostou et al, 2011(Anagnostou et al, , 2012Blamart et al, 2007;McCulloch et al, 2012;Rollion-Bard et al, 2011a, b;Thresher et al, 2011). Coral uranium to calcium (U / Ca) ratios are known to depend on the carbonate system parameters (Anagnostou et al, 2011;Inoue et al, 2011;Min et al, 1995;Shen and Dunbar, 1995;Swart and Hubbard, 1982). Initial studies showed that coral U / Ca ratios are related to seawater temperature (Min et al, 1995;Shen and Dunbar, 1995), but also suggested that seawater pH may also play an important role in the incorporation of uranium into the skeleton of tropical corals.…”
Section: Introductionmentioning
confidence: 99%
“…One coral specimen (452K1) was analysed geochemically using LA-ICP-MS (Böcker, 2014) with regard to concentrations of environmentally sensitive elements (e.g. Sr / Ca, U / Ca, B / Ca) and following recommendations for evaluating the diagenetic status of corals from strongly lithified and altered limestone (Anagnostou et al, 2011;Gothmann et al, 2015). LA-ICP-MS analyses were performed at the Max Planck Institut für Chemie (Mainz, Germany) using a NewWave UP 213 laser ablation system coupled to a ThermoFisher Element 2 ICP-MS.…”
Section: Methodsmentioning
confidence: 99%
“…According to our conviction, all these data provide no critical evidence for the alteration of the original skeleton. Because of this line of reasoning and low overall calcite content evident from XRD analysis (calcite below detection limits), we refrained from measuring element ratios sensitive to the redox conditions of calcite precipitating freshwaters or burial fluids (Fe / Ca, Mn / Ca) and other more sophisticated geochemical methods as potential measures of alteration (Anagnostou et al, 2011;Gothmann et al, 2015).…”
Section: Preservationmentioning
confidence: 99%
See 1 more Smart Citation